The Effects of Counterproductive Workplace Behaviors on Academic LIS Professionals’ Health and Well-Being - Fic, Christy; Albro, Maggie (Evidence Based Library and Information Practice, 2022)
Objective – This study seeks to investigate the degree of counterproductive workplace behaviors (CWB) experienced by library and information science (LIS) professionals and how these behaviors contribute to physical, mental, and chronic health outcomes. While health outcomes may be present independent of CWB, this study seeks to explore the relationship between the two to provide context to the growing incidence of burnout among academic LIS professionals.Methods – This quantitative study analyzed 327 responses to a survey about colleague behavior and health sent to LIS professionals through library community electronic mailing lists. The survey contained demographic questions, questions about CWB, questions about health experiences, and questions about the perceived relationship between work and health. Counterproductive workplace behaviors were rated on a seven-point Likert scale. A behavior score was calculated by adding the Likert values of the 12 behavior questions. This score was used when comparisons about CWB were compared by demographics and health responses. Statistical analysis of survey results was performed using RStudio.Results – The mean total behavior score was 39. 107 respondents’ total behavior scores fell in the low range, 202 in the moderate range, and 18 in the high range. There was no significant relationship found between demographic factors and behavior score. A negative relationship was observed between duration of employment in an academic library and presence of mental health issues (F(5, 310) = 10.114, p = 5.5e-09). A similar relationship was observed between duration of employment in the respondents’ current library and presence of mental health issues (F(5, 311) = 9.748, p = 1.15e-08). Level of CWB experienced was found to have a relationship with the perceived ability to maintain good mental (F(2, 324) = 36.34, p = 5.75e-15), physical (F(2, 324) = 23.82, p = 2.24e-10), and chronic health (F(2, 323) = 13.04, p = 3.57e-06). Generally speaking, lower levels of CWB were associated with fewer challenges maintaining health.Conclusion – Low to moderate levels of CWB are common in academic libraries. These behavior levels are associated with an increase in health challenges. LIS professionals perceive work as being a factor that contributes to having trouble maintaining good mental and physical health and toward successfully managing chronic health conditions. Further study is needed to determine the degree to which experiencing CWB in the workplace affects health. Further study is also needed to determine if certain behaviors impact health outcomes more than others.